If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5x + -8) + -6x + 20 = -22 Reorder the terms: 3(-8 + 5x) + -6x + 20 = -22 (-8 * 3 + 5x * 3) + -6x + 20 = -22 (-24 + 15x) + -6x + 20 = -22 Reorder the terms: -24 + 20 + 15x + -6x = -22 Combine like terms: -24 + 20 = -4 -4 + 15x + -6x = -22 Combine like terms: 15x + -6x = 9x -4 + 9x = -22 Solving -4 + 9x = -22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 9x = -22 + 4 Combine like terms: -4 + 4 = 0 0 + 9x = -22 + 4 9x = -22 + 4 Combine like terms: -22 + 4 = -18 9x = -18 Divide each side by '9'. x = -2 Simplifying x = -2
| X+99=93 | | 4(3r-4)=3(r+9)+2 | | b-1/2=2 | | 3(Y+9)+3Y=30 | | 10+6a=-104 | | f(x)=3x^2+5x+7 | | X/2-430 | | 2(t+8)=8 | | 9x-6=7y+3x | | 5y+6q=20 | | 200+.62x=379.8 | | 4x^2-10x-126=0 | | 2x-x=-1+3 | | 200-.62x=379.8 | | 24a^3b^2-16a^2b^3/8ab | | 5y-8/8-5y | | 5(4a+3b)5(2a+3b)= | | 2/5x-1-9/4x-6 | | 25x-21=16x-4x | | 3(y+9)1y=30 | | (2x-5)/(x-1)3 | | sin(2x)-(.259)=cos(x)-(.978) | | Y=-x/4-3 | | 9(t+5)=5 | | 6x^2+4x+7=7 | | (2x-5/x-1)3 | | -3d=36 | | 7+ax-9=-6 | | X-2/5=3.5 | | (2h-3i)(h+4i)= | | 71.4=6(m+3.6) | | 2(3(1.6)+2)=2x-1+x |